Jacques Cousteau and the undersea world - King, Roger (Philadelphia : Chelsea House Publishers, 2001)
A biography of the French marine explorer who pioneered skin diving after helping perfect the aqualung underwater breathing device.
Includes bibliographical references (p. 62) and index.
School Library Journal.
Book Report.
6.2
5-8
Keywords: Cousteau, Jacques Yves -- Juvenile literature; Cousteau, Jacques Yves; Cousteau, Jacques Yves; Oceanographers -- France -- Biography -- Juvenile literature; Explorers -- France -- Biography -- Juvenile literature; Oceanographers; Explorers; Oceanographers -- Biography; Explorers -- Biography; Oceanographers; Explorers -- Biography; Underwater exploration